GAYA BAHASA IKLAN PRODUK KESEHATAN DAN KOSMETIK PADA HARIAN PAGI POSMETRO PADANG - Agusmanto Agusmanto; Ermanto Ermanto; Ermawati Arief Ermawati Arief (Jurnal Bahasa dan Sastra, 2013)
This study focused on the use of language style health products and cosmetics advertisements in Harian Pagi Posmetro Padang. This research is descriptive qualitative research method that aims to describe the style of the language of advertising in print media. The results of this research are health and cosmetic product advertising on Harian Pagi Posmetro Padang. Data obtained from Harian Pagi Posmetro Padang, published during September to November in 2011 which consisted of two ads beauty and health advertising eight. Based on the research results, we can conclude two things, namely (1) the language style of the language contained in the advertisement Harian Pagi Posmetro Padang is personification, metaphor, simile, hyperbole, paradox, inuendo, cynicism, sarcasm, and metonymy. (2) from eight style that is found in Harian Pagi Posmetro Padang, the dominant style of language used is style personified.